Recycling activities: awareness among students at School of Business and Economics and School of Psychology and Socials at University Malaysia Sabah (UMS) / Nur Syahadah Ahmad Amin - Ahmad Amin, Nur Syahadah (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2010)
This research was done in order to study the case study Recycling Activities: Awareness among students at School of Business and Economics and School of Psychology and Socials at University Malaysia Sabah. This research objective is want to see the awareness, attitude and the feedback of the willingness among students towards of the recycling activities.